THE INFLUENCE OF INSTAGRAM SOCIAL MEDIA ON TOURIST VISITING INTERESTS (CASE STUDY IN CIBEUSI TOURISM VILLAGE, CIATER DISTRICT, SUBANG REGENCY) - Bismantara Bismantara; Bedy Andriansyah (DIMENSIA (Diskursus Ilmu Manajemen STIESA), 2024)
Social media plays an important role in modern human life, not only as a means of communication but also as a platform for sharing information and experiences. Instagram, as one of the most popular social media platforms, has become an effective tool in promoting tourist destinations, which tends to have an impact on tourist interest in visiting. The purpose of this study was to determine and measure the extent to which Instagram social media influences tourist interest in visiting, with a case study focus on Cibeusi Tourism Village, Ciater District, Subang Regency. The unit of analysis of this study is tourists in Subang Regency in 2024. The method in this study uses quantitative data and descriptive verification statistics. The sampling technique used questionnaires, literature studies and observations using 80 respondents from tourists in Subang Regency. The analysis tests used in this study were classical assumption tests, simple linear regression tests, and hypothesis tests using the SPSS program. The results of this study based on the results of a survey of Instagram social media influencing visiting interest by 61.5%, it can be concluded that Instagram social media for tourists in Subang Regency is very good.